2015
DOI: 10.1038/jcbfm.2015.178
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Silent Information Regulator 2 (SIRT2) Preserves Neurological Function after Experimental Stroke in Mice

Abstract: Sirtuin-2 (Sirt2) is a member of the NAD(+)-dependent protein deacetylase family. Various members of the sirtuin class have been found to be involved in processes related to longevity, regulation of inflammation, and neuroprotection. Induction of Sirt2 mRNA was found in the whole hemisphere after experimental stroke in a recent screening approach. Moreover, Sirt2 protein is highly expressed in myelin-rich brain regions after stroke. To examine the effects of Sirt2 on ischemic stroke, we induced transient focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…It has been reported that SIRT2 inhibition can decrease the injury in cellular and animal models of PD, HD [8] and ischemia stroke [9]. Since inflammation plays critical pathological roles in these diseases [13][14][15] and SIRT2 is necessary for bacteria infection [6], we hypothesized that SIRT2 may be important for neuroinflammation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that SIRT2 inhibition can decrease the injury in cellular and animal models of PD, HD [8] and ischemia stroke [9]. Since inflammation plays critical pathological roles in these diseases [13][14][15] and SIRT2 is necessary for bacteria infection [6], we hypothesized that SIRT2 may be important for neuroinflammation.…”
Section: Resultsmentioning
confidence: 98%
“…SIRT2 inhibition or deficiency has been shown to produce neuroprotective effects in models of both neurodegenerative diseases [8] and ischemia stroke [9]: SIRT2 inhibition led to a decrease in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage [10]; SIRT2 deletion was shown to decrease α-synuclein-induced neurotoxicity in models of Parkinson's disease [11]; SIRT2 inhibitor AK-7 was shown to produce beneficial effects in a mouse model of HD [12]; and SIRT2 deficiency mice also showed decreased neurological deficits after ischemia stroke [9]. However, it is warranted to investigate the mechanisms underlying the neuroprotective effects of SIRT2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Results in cerebral ischemia are less clear [186, 190]. However, SIRT2 has also been shown to contribute to the pathology of the vascular system and to the effects of oxidative stress in the endothelium, which have immediate impact on brain oxygen supply [191, 192].…”
Section: Sirtuins In Neurodegeneration and Neuroprotectionmentioning
confidence: 99%
“…The lack of neuroprotection in a model of ischemic stroke with pharmacological or genetic inhibition of Sirt2 is in direct contrast to our observations with the protection observed with AGK2 in our mouse CA/CPR model (Chen et al, 2015). Interestingly, while Sirt2 knockout mice did not display histological benefit following ischemic stroke, they had improved functional outcome compared to wild-type mice (Krey et al, 2015). Oxidative stress is a common injury mechanisms in many neurodegenerative disease, particularly those resulting from cerebral ischemia and TRPM2 is a well-established mediator of oxidative cell death (Belrose et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sirt2 is a cytosolic protein that is expressed in many cell types and tissues throughout the body including the central nervous system. Expression of Sirt2 is observed in neurons as well as oligodendrocytes, microglia and astrocytes (Krey et al, 2015). Sirt2 has been demonstrated to contribute to neurodegeneration in models of Parkinson’s and Huntington’s disease (Donmez, 2013).…”
Section: Introductionmentioning
confidence: 99%